The Local Impact of Migratory Legends: The Process and Function of Localisation - Ambrož Kvartič (Journal of Ethnology and Folkloristics)
Folk narratives are one of the mechanisms by which humans form their cultural reality; and space is an important part of this reality. In the majority of examples, contemporary legends do not explicitly refer to individual elements of the local space, however the messages that they convey are always placed in the local environment, i.e. the space that the legend-bearers directly perceive and evaluate. This placement of the folklore material is enabled by the process of the localisation of motifs. Legends that are treated as migratory due to their general geographical extensiveness can convey their message, and thus fulfil their role, only by the inclusion of an element occurring in actuality of the given space. On the level of content, in contemporary legends the local space is presented primarily as the backdrop of the events, and the fact that it is stated at all creates the impression of the apparent closeness of the events described, which enables an even stronger effect. Thus, the contemporary legends about foreigners in Velenje, which at their core are stories about the Other, are also characterised by their experiential backdrop.